Major depressive disorder and the microbiome-gut-brain axis - F. H. Ouriaghli; I. A. Elhaty (The Ukrainian Biochemical Journal)
The central nervous system and the gastrointestinal tract are connected bidirectionally via the gut-brain axis (GBA). According to the gut microbiota hypothesis, changes in the composition and activity of the gut microbiota can affect the GBA, contributing to the onset of mental illnesses such as depression and anxiety. This review aims to analyze how microbiota imbalances can affect the functioning of the gut-brain axis, causing changes in metabolism, immune system and neurotransmitters that are associated with depression. The potential of dietary modifications, probiotics, prebiotics and symbiotics to restore microbiota balance as well as the importance of microbiota profiling integration into personalized clinical practice are discussed.